Epigenetic Modulators of Monocytic Function: Implication for Steady State and Disease in the CNS - Papavasiliou, F. Nina; Chung, Young Cheul; Gagnidze, Khatuna; Hajdarovic, Kaitlyn H.; Cole, Dan C.; Bulloch, Karen (Frontiers in Immunology, 2016)
Epigenetic alterations are necessary for the establishment of functional and phenotypic diversity in populations of immune cells of the monocytic lineage. The epigenetic status of individual genes at different time points defines their transcriptional responses throughout development and in response to environmental stimuli. Epigenetic states are defined at the level of DNA modifications, chromatin modifications, as well as at the level of RNA base changes through RNA editing. Drawing from lessons regarding the epigenome and epitranscriptome of cells of the monocytic lineage in the periphery, and from recently published RNAseq data deriving from brain-resident monocytes, we discuss the impact of modulation of these epigenetic states and how they affect processes important for the development of a healthy brain, as well as mechanisms of neurodegenerative disease and aging. An understanding of the varied brain responses and pathologies in light of these novel gene regulatory systems in monocytes will lead to important new insights in the understanding of the aging process and the treatment and diagnosis of neurodegenerative disease.